A mechanical approach to explain cortical folding phenomena in healthy and diseased brains - Budday, Silvia; Steinmann, Paul; Kuhl, Ellen (PAMM, 2014)
The development of the human brain with its characteristically folded surface morphology remains an intensively discussed topic. Impressive advancements in different fields of research have enhanced the understanding of the brain. However, the mechanism that underlies the folding process in healthy and diseased brains remains undetermined. Here, we hypothesize that growth induced mechanical instabilities drive folding. Using the nonlinear field theories of continuum mechanics supplemented by the theory of finite growth [1], we model the human brain as a bi-material with the cerebral cortex, a morphogenetically growing outer layer of gray matter, and the subcortex, a strain-driven growing inner core of white matter [2]. This approach integrates the two popular but competing hypotheses that cortical folding is either driven by differential growth or by axon elongation. Through systematic sensitivity analyses, we identify the critical process parameters of cortical folding and quantify their impact on brain morphology. We further simulate phenomena causing malformations like lissencephaly and polymicrogyria [3], which are associated with neurological disorders, including severe retardation, epilepsy, schizophrenia, and autism. Understanding the mechanisms of cortical folding during brain development might facilitate the diagnostics and treatment of malformed brains. (© 2014 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim)
UnivIS-Import:2015-07-08:Pub.2014.tech.FT.FT-TM.amecha_7